1995
DOI: 10.1038/377344a0
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of GABAA receptors by tyrosine phosphorylation

Abstract: gamma-Aminobutyric acid type-A (GABAA) receptors are the major sites of fast synaptic inhibition in the brain. They are presumed to be pentameric heteroligomers assembled from four classes of subunits with multiple members: alpha (1-6), beta (1-3), gamma (1-3) and delta (1). Here, GABAA receptors consisting of alpha 1, beta 1 and gamma 2L subunits, coexpressed in mammalian cells with the tyrosine kinase vSRC (the transforming gene product of the Rous sarcoma virus), were phosphorylated on tyrosine residues wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

10
156
2
2

Year Published

1996
1996
2007
2007

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 209 publications
(170 citation statements)
references
References 22 publications
10
156
2
2
Order By: Relevance
“…The internal versus surface expression of GABA A receptors in the postsynaptic sites needs to be examined to determine CaN-mediated GABA A receptor trafficking to and from the cell surface that is therefore likely to be an important mechanism for expression of LTD at inhibitory synapses. In addition to adaptin, there has been a report that tyrosine kinase Src modulates neuronal as well as recombinant GABA A receptors to enhance receptor channel activity (Moss et al, 1995). Src kinase also phosphorylates both Y 365 and Y 367 residues of the ␥ 2L (long form) subunit (Moss et al, 1995).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The internal versus surface expression of GABA A receptors in the postsynaptic sites needs to be examined to determine CaN-mediated GABA A receptor trafficking to and from the cell surface that is therefore likely to be an important mechanism for expression of LTD at inhibitory synapses. In addition to adaptin, there has been a report that tyrosine kinase Src modulates neuronal as well as recombinant GABA A receptors to enhance receptor channel activity (Moss et al, 1995). Src kinase also phosphorylates both Y 365 and Y 367 residues of the ␥ 2L (long form) subunit (Moss et al, 1995).…”
Section: Discussionmentioning
confidence: 99%
“…In addition to adaptin, there has been a report that tyrosine kinase Src modulates neuronal as well as recombinant GABA A receptors to enhance receptor channel activity (Moss et al, 1995). Src kinase also phosphorylates both Y 365 and Y 367 residues of the ␥ 2L (long form) subunit (Moss et al, 1995). By specifically blocking the association of Src with the GABA A receptor ␥ 2 subunit (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…In this respect, there seems to be a time lag between elevation of [Ca 2ϩ ] i and BDNF-induced reduction of the amplitude of IPSCs, suggesting the involvement of activation of some signal cascade after the rise in [Ca 2ϩ ] i . GABA A receptor function is maintained by phosphorylation and disrupted by [Ca 2ϩ ] i elevation (Stelzer et al, 1988;Marchenko, 1991;Gyenes et al, 1994;Moss et al, 1995). In this respect, dephosphorylation induced by a Ca 2ϩ -dependent phosphatase may be involved in the downstream of BDNF-activated signal transduction and lead to the attenuation of GABA A response (Stelzer and Shi, 1994;Chen and Wong, 1995).…”
Section: Involvement Of Intracellular Ca 2؉ Mobilizationmentioning
confidence: 99%
“…Evidence has been accumulating for some years now that tyrosine kinases are involved in receptor-mediated current inhibition, and in contraction and cell-signalling (Williams, 1989;Tsuda. et al, 1991;Wijetunge et al, 1992;Huang et al, 1993;Hollenberg, 1994;Felder, 1995;Wang & Salter, 1994;Moss et al, 1995;Wijetunge & Hughes, 1995;Hatakeyama et al, 1996). These studies suggest tyrosine phosphorylation of tyrosine residues might be an important mechanism for channel regulation, in addition to the well-attested protein phosphorylation that occurs through serine/threonine kinases.…”
Section: Introductionmentioning
confidence: 99%
“…These studies suggest tyrosine phosphorylation of tyrosine residues might be an important mechanism for channel regulation, in addition to the well-attested protein phosphorylation that occurs through serine/threonine kinases. It has also been found that various channels can be phosphorylated by tyrosine kinase and the e ect inhibited by tyrosine kinase inhibitors (Huang et al, 1993;Moss et al, 1995;Lev et al, 1995;Swope et al, 1995).…”
Section: Introductionmentioning
confidence: 99%